Women's movements in Asia : feminisms and transnational activism - Edwards, Louise P.; Roces, Mina, 1959- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2010)
"Women's Movements in Asia is a comprehensive study of women's activism across Asia. With chapters written by leading international experts, it provides a full overview of the history of feminism, as well as the current context of the women's movement in 12 countries: the Philippines, China, Indonesia, Japan, Burma, Singapore, Vietnam, Malaysia, Thailand, Cambodia, Hong Kong, Korea, India and Pakistan.
For each of these countries the manner in which feminism changes according to cultural, political, economic and religious factors is explored. The contributors investigate how national feminisms are influenced by transnational factors, such as the women's movements in other countries, colonialism and international agencies. Each chapter also considers what Asian feminists have contributed to global theoretical debates on the woman question, the key successes and failures of the movements and what needs to be addressed in the future."--pub. desc.
Asian feminisms : women's movements from the Asian perspective / Mina Roces -- Feminism and the women's movement in the world's largest Islamic nation / Susan Blackburn -- Rethinking 'the Filipino woman' : a century of women's activism in the Philippines, 1905-2006 / Mina Roces -- Chinese feminism in a transnational frame : between internationalism and xenophobia / Louise Edwards -- Transnational networks and localized campaigns : the women's movement in Singapore / Lenore Lyons -- Crossing boundaries : transnational feminisms in twentieth-century Japan / Barbara Molony -- Feminism, Buddhism and transnational women's movements in Thailand / Monica Lindberg Falk -- Following the trail of the fairy-bird : the search for a uniquely Vietnamese women's movement / Alessandra Chiricosta -- Hong Kong women's movement : towards a politics of difference and diversity / Adelyn Lim -- Military rule, religious fundamentalism, women's empowerment and feminism in Pakistan / Andrea Fleschenberg -- Mapping a hundred years of activism : women's movements in Korea / Seung-Kyung Kim and Kyounghee Kim -- 'Riding a buffalo to cross a muddy field' : heuristic approaches to feminism in Cambodia / Trudy Jacobsen -- Rights talk and the feminist movement in India / Sumi Madhok.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Feminism -- Asia; Women -- Political activity -- Asia; Transnationalism; Electronic books